2020
DOI: 10.1002/adfm.202002046
|View full text |Cite
|
Sign up to set email alerts
|

2D Covalent Organic Frameworks for Biomedical Applications

Abstract: Covalent organic frameworks (COFs) are an emerging class of organic crystalline polymers with welldefined molecular geometry and tunable porosity. COFs are formed via reversible condensation of lightweight molecular building blocks which dictate its geometry in two or three dimensions. Among COFs, two-dimensional COFs (2D COFs) have garnered special attention due to their unique structure composed of two-dimensionally extended organic sheets stacked in layers generating periodic columnar π-arrays, functional p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
139
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 200 publications
(144 citation statements)
references
References 225 publications
(211 reference statements)
0
139
0
1
Order By: Relevance
“…Interestingly, this method provides a wide range of crystallinity and controlled porosity of COFs, however, the rate of reaction is slow. [ 58,59 ] Ding et al. investigated different types of solvent and their ratio for the synthesis of boronate ester linkages of COF (NiPc COF) in solvothermal condition.…”
Section: Strategies For the Synthesis Of Cofsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, this method provides a wide range of crystallinity and controlled porosity of COFs, however, the rate of reaction is slow. [ 58,59 ] Ding et al. investigated different types of solvent and their ratio for the synthesis of boronate ester linkages of COF (NiPc COF) in solvothermal condition.…”
Section: Strategies For the Synthesis Of Cofsmentioning
confidence: 99%
“…Readers are encouraged to refer to S. Lohse et al., [ 84 ] Sharma et al., [ 59 ] Geng et al., [ 85 ] and Bhunia et al. [ 58 ] for detailed synthesis procedures for the COFs discussed above.…”
Section: Strategies For the Synthesis Of Cofsmentioning
confidence: 99%
“…Researchers have recently discovered the potential of COFs for use in biomedical applications, such as drug delivery and cancer therapy [ 270 , 271 , 272 ]. The high porosity, pore volume and surface area typically observed in synthesized COF structures allow for high drug loading capacity, making them good candidates as drug delivery agents.…”
Section: Cof Applicationsmentioning
confidence: 99%
“…Characterization showed that the CPT ligand increased hydrophobicity of the material, therefore increasing COF stability in water—an important aspect to consider as boronate ester COFs are particularly susceptible to hydrolysis. More importantly, the CPT-COF conjugate was observed to be easily internalized by cell membranes and showed higher cytotoxic activity than the free drug, even at low doses [ 273 ], adding another example to a vastly growing amount of reports of COF materials as promising drug delivery agents [ 271 , 274 , 275 , 276 , 277 ]. Guan et al designed and prepared a functionalized COF nanocomposite for highly selective synergistic tumor therapy [ 278 ].…”
Section: Cof Applicationsmentioning
confidence: 99%
“…Highly ordered and solid‐state porous two‐dimensional (2D) nanomaterials are a new class of materials (Karak et al, 2017; Karak, Kumar, Pachfule, & Banerjee, 2018; Zhang et al, 2019), that have shown wide‐spread applications in catalysis (Chen, Zhang, Jiao, & Jiang, 2018), sensing (Das et al, 2015; Ding et al, 2016; Ma et al, 2018), biomedical (Fang, Kim, Kim, & Yu, 2013; Yang, Léonard, Lemaire, Tian, & Su, 2011), gas adsorption (Ma et al, 2018; Zhu et al, 2017), and energy storage (Kou et al, 2017). These 2D nanomaterials include graphitic carbon nitride (g‐C 3 N 4 ) (Wang, Zhang, Li, Li, & Wu, 2017; Zhang et al, 2013), transition metal dichalcogenides (TMDs; Carrow et al, 2020; Jaiswal, Singh, Lokhande, & Gaharwar, 2019; Lu, Yu, Ma, Chen, & Zhang, 2016; Zhang, Lai, Ma, & Zhang, 2018), covalent organic frameworks (COFs; Bhunia, Deo, & Gaharwar, 2020), hexagonal boron nitride (h‐BN; Deshmukh, Jeong, Lee, Park, & Kim, 2019; He et al, 2019), layered double hydroxides (LDHs; Yu, Wang, O'Hare, & Sun, 2017; Zhao et al, 2017), layered silicates (nanoclay) (Gaharwar et al, 2019), polymer sheets (Clover et al, 2020), and noble metal nanosheets (Huang et al, 2011; Sancho‐Albero et al, 2019). Diverse biomedical applications of these nanomaterials are owing to their versatile properties including high surface area, high conductivity, and superior optical properties (Brokesh & Gaharwar, 2020; Chimene, Alge, & Gaharwar, 2015; Gaharwar, Singh, & Khademhosseini, 2020; Lee & Gaharwar, 2020).…”
Section: Introductionmentioning
confidence: 99%